Cloudy with a chance of meatballs - Barrett, Judi.; Barrett, Ron (New York : Aladdin Books ; London : Collier Macmillan, 1982)
Life is delicious in the town of Chewandswallow where it rains soup and juice, snows mashed potatoes, and blows storms of hamburgers--until the weather takes a turn for the worse.
Booklist
New York Times Book Review
National Council Of Teachers Of English
3.2
K-3
Keywords: Weather -- Fiction; Food -- Fiction; Weather -- Fiction; Food -- Fiction; Humorous stories